Emerging Travel Trends: Joy of Missing Out (JOMO) Vs Iconic Landmarks - Fajar Kusnadi Kusumah Putra (Jurnal Pariwisata Terapan, 2019)
Tourism derived from many criteria ranging from activities, attractions, location, travel style and the tourism product category preferred. The present paper aimed to examine the two travel trends The Joy of Missing Out (JOMO) and Iconic landmarks and sites by reviewing relevant literature review from both travel trends, and critically analyse which of one of the two trends is likely to dominate. A comparison of the two trends reveals that JOMO is a type of journey that emphasises with the isolation against technology, with motivation for relaxation, escape from everyday routine and commitments. Meanwhile, iconic landmarks and sites travel trends have the characteristics in novelty seeking to visit exciting places, viewing the scenery and related to tourist self-development. These studies provide valuable insights into the JOMO concept related to the motivation of relax and iconic landmarks and sites tourist attraction described as a ‘flagship, which is highly noticeable as the strongest pull-factors of a destination and regarded a primary growth destination resource. The scope of this study was limited in terms of travel trends from the literature review. Further studies need to be carried out in order to validate the experiences of the traveller within these two travel trends by comparing their expectations, perceptions, and motives.